Accuracy of Body Mass Index-defined Obesity Status in US Firefighters - Nattinee Jitnarin; Walker S.C. Poston; Christopher K. Haddock; Sara A. Jahnke; Rena S. Day (Elsevier, 2014)
Obesity is a significant problem affecting United States (US) firefighters. While body mass index (BMI) is widely used to diagnose obesity, its use for this occupational group has raised concerns about validity. We examined rates and types of misclassification of BMI-based obesity status compared to body fat percentage (BF%) and waist circumference (WC). Male career firefighters (N = 994) from 20 US departments completed all three body composition assessments. Mean BMI, BF%, and WC were 29 kg/m2, 23%, and 97 cm, respectively. Approximately 33% and 15% of BF%- and WC-defined obese participants were misclassified as non-obese (false negatives) using BMI, while 8% and 9% of non-obese participants defined by BF% and WC standards were identified as obese (false positives) using BMI. When stratified by race/ethnicity, Pacific Islanders showed high rates of false positive misclassification. Precision in obesity classification would be improved by using WC along with BMI to determine firefighters' weight status.